Investigating female learners’ attitude and challenges towards mathematics at the department of mathematics, Injibara college of teachers’ education, Injibara, Ethiopia - Workineh Kebede (Cogent Education, 2023)
AbstractThe main purpose of this research was to investigate the current status of female students’ attitude and challenges towards mathematics at the Department of Mathematics, Injibara College of Teachers’ Education (henceforth, Injibara CTE). The mixed methods approach with concurrent embedded strategy and descriptive survey design were used. A questionnaire survey was administered to 85 female mathematics department students using a comprehensive sampling technique. Moreover, face-to-face interviews were administered to the mathematics department head and the college deans purposively to gather pertinent data about the challenges female students face when learning mathematics. Both quantitative (mean, standard deviation, t-test, and post hoc test) and qualitative (thematic analysis and narration) data analysis techniques were employed. Cronbach’s alpha coefficients for internal consistency reliability were calculated and reported to ensure the instrument validity. The main findings of this study were that female students in the department of mathematics had positive attitude toward mathematics on an overall and component-by-component basis (affective, cognitive, and behavioral). Moreover, they had shown a positive attitude across pre-service and in-service training programs. There was a statistically significant difference in attitude between the two programs in favor of the pre-service program. The challenges female students faced with learning mathematics were student-related, teacher-related, peer-related, material resource-related, and administrative-related. Recommendations include: mathematics teachers should encourage female students and use appropriate teaching methods, instructional media, and assessment techniques; college administration should provide material resources needed for mathematics learning; and additional research shall be conducted in this area to ensure validity and reliability.